Identifying changes in soybean protein properties during high-moisture extrusion processing using dead-stop operation. Issue 17 (30th November 2022) - Meng, Ang; Chen, Fengliang; Zhao, Donglin; Wei, Yimin; Zhang, Bo
Highlights: Dead-stop operation can provide more evidence for the fibrous formation process. Surface hydrophobicity of the protein was the lowest in zone 1 with water injection. The lowest value of extractable protein was in zone 3 (150 °C). The protein ΔH was reduced from feeding zone to zone 3 and recovered in cooling die. The secondary structure of protein was more ordered after than before extrusion. Abstract: To provide additional evidence and better understand the high-moisture texturing extrusion process of soybean protein isolate (SPI), the physico-chemical changes of SPI during extrusion were investigated. SPI in the extruder feeding zone, barrel zones 1 (80 °C) to 4 (135 °C), and the cooling die (80 °C) were obtained from a dead-stop operation. The lowest values associated with the denaturation enthalpy and the extractable protein occurred in zone 3 (150 °C). The minimum level of the protein subunit content was identified in zone 4. The highest value of the average protein molar mass occurred in zone 3. The β-sheet ratio in the protein increased, and the unordered ratio decreased after extrusion. The surface hydrophobicity of the protein decreased with water injection in zone 1; however, it increased in zone 2 (110 °C). Overall, SPI undergoes swelling, denaturation, aggregation, and depolymerization due to water injection, heating, and shearing during high-moisture extrusion.